Learning Ceph : a unified, scalable, and reliable open source storage solution - D'Atri, Anthony; Singh, Karan; Bhembre, Vaibhav (Packt Publishing, 2017)
Implement and manage your software-defined, massively scalable storage system About This Book Explore Ceph's architecture in order to achieve scalability and high availability Learn to utilize Ceph efficiently with the help of practical examples Successfully implement Ceph clusters to scale-out storage solutions along with outstanding data protection Who This Book Is For A basic knowledge of GNU/Linux, and storage systems, and server components is assumed. If you have no experience of software-defined storage solutions and Ceph, but are eager to learn about them, this is the book for you. What You Will Learn The limitations of existing systems and why you should use Ceph as a storage solution Familiarity with Ceph's architecture, components, and services Instant deployment and testing of Ceph within a Vagrant and VirtualBox environment Ceph operations including maintenance, monitoring, and troubleshooting Storage provisioning of Ceph's block, object, and filesystem services Integrate Ceph with OpenStack Advanced topics including erasure coding, CRUSH maps, and performance tuning Best practices for your Ceph clusters In Detail Learning Ceph, Second Edition will give you all the skills you need to plan, deploy, and effectively manage your Ceph cluster. You will begin with the first module, where you will be introduced to Ceph use cases, its architecture, and core projects. In the next module, you will learn to set up a test cluster, using Ceph clusters and hardware selection. After you have learned to use Ceph clusters, the next module will teach you how to monitor cluster health, improve performance, and troubleshoot any issues that arise. In the last module, you will learn to integrate Ceph with other tools such as OpenStack, Glance, Manila, Swift, and Cinder. By the end of the book you will have learned to use Ceph effectively for your data storage requirements. Style and approach This step-by-step guide, including use cases and examples, not only helps you to easily use Ceph but also demonstrates how you can use it to solve any of your server or drive storage issues. Downloading the example code for this book. You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com . If you purchased this book elsewhere, you can visit http://www.PacktPub.com/support and register to have the code file.